2008
DOI: 10.1590/s0102-09352008000200025
|View full text |Cite
|
Sign up to set email alerts
|

Performance and morphology of intestinal mucosa of broilers fed mannan-oligosaccharides and enzymes

Abstract: Performance and morphology of intestinal mucosa of broilers fed mannan-oligosaccharides and enzymes ABSTRACTThe performance and the morphology of intestinal mucosa of broilers fed mannan-oligosaccharides (MOS) and enzymes (E) from one to 21-day-old were evaluated using 750 one-day-old chicks, assigned to a 2 x 2 + 1 factorial design -two levels of MOS (0 and 0.1%), two levels of E (0 and 0.05%) plus an antibiotic positive control diet -performing five treatments of five replications each one. MOS x E interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
2
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 16 publications
(1 reference statement)
3
20
2
5
Order By: Relevance
“…On the other hand, antibiotic supplementation caused a decrease in ileal villi height. Similar results were reported by Oliveira et al (2008), who found that antibiotic supplementation caused low villi height. They explained this by the suppressing effect of the antibiotic on beneficial bacteria in the gut, such as Lactobacillus and Bifidobacteria.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, antibiotic supplementation caused a decrease in ileal villi height. Similar results were reported by Oliveira et al (2008), who found that antibiotic supplementation caused low villi height. They explained this by the suppressing effect of the antibiotic on beneficial bacteria in the gut, such as Lactobacillus and Bifidobacteria.…”
Section: Discussionsupporting
confidence: 90%
“…Considering that lactulosis is a non-digestible disaccharide with prebiotic action, the results were different from the results obtained by Oliveira et al (2008), who utilized a mannan-oligosaccharide in diet for broilers and observed increment in jejunum villous height.…”
Section: Resultscontrasting
confidence: 89%
“…Salmonellae belongs to the group of enteropathogens that are commercial barriers to poultry products and present extremely important serovars to public health (Marcus et al, 2007;Perdoncini et al, 2011). In these serovars, S. Typhimurium stands out as a source of feed toxinfections in humans (Fernandes et al, 2006), and its control is officially recognized by the Brazilian Plan of Poultry Health Control.…”
Section: Introductionmentioning
confidence: 99%
“…The intestinal epithelial cells are change constantly and compensate villi cells losses through proliferation and maturation inside crypts and upward migration. The crypts depth was correlated with the intestinal cells turnover rate and the increase in crypts depth indicates the need for enterocyte replacement and higher tissue turnover [31]. The crypt depth may be an important factor that determines the ability of the crypts to sustain the increase in the villus height as well as to maintain the villus structure [32].The ratio of villus 30.09 ± 1.90 The different letters in one raw denoted that there were significant differences between male and female indigenous ducks, in all traits at p≤0.01.…”
Section: Histological Results and Discussionmentioning
confidence: 99%